Cryptocurrencies: bitcoin and its growing regulation. A look into the future - Gutiérrez Proenza, Janetsy (2023)
The great influences of cryptocurrencies, essentially by Bitcoin has promoted a rapid development of technologies tending to an incredible growth since 2013. However, this frantic acceleration of the processes of consolidation of cryptocurrencies as an alternative to the financial system established around the world, has generated great uncertainty or distrust for this new system that implies a different knowledge about financial and transactional processes, above all, due to the deconcentrating  of the use and regulation of the currency by central institutions, in addition to the lack of an entity, be it State or World Banks for the control and / or regulation of this phenomenon. What  is the global trend that the future holds for this type of commercial transaction? What regulatory incidences are observed in Ecuador and in the world? Is a normative order needed to protect the users who occupy them and the social effect they have produced? These are some of the questions that are intended to be answered in this article.